A Brief Study of Binaural Beat: A Means of Brain-Computer Interfacing - A. F. M. Zainul Abadin; Ahmed Imtiaz; Md. Manik Ahmed; Mithun Dutta (Advances in Human-Computer Interaction)
The human brain tends to follow a rhythm. Sound has a significant impact on our physical and mental health. This sound technology uses binaural beat by generating two tones of marginally different frequencies in each individual ear to facilitate the improved focus of attention, emotion, calming, and sensory organization. Binaural beat helps in memory boosting, relaxation, and work performance. Again because of hearing a binaural beat sound, brainwave stimuli can be diagnosed to pick up a person’s sensitive information. Using this technology in brain-computer interfacing, it is possible to establish a communication between the brain and the computer. Thus, it enables us to go beyond our potential. The aim of this study is to assess the impact and explore the potential contribution of binaural beat to enhancement of human brain performance.